Pengaruh Lingkungan Kerja Dan Motivasi Kerja Terhadap Produktivitas Karyawan Pada PT XYZ - Silaban, Norberta Tarida Nurcahaya; Aprillia, Frida; Siboro, Sonny Fransisco (CV Warnak Johanna Nusantara, 2026)
Employee productivity is a key factor in a company's success in facing increasingly intense competition. Work environment and work motivation are the main factors that influence productivity; however, previous research results have been inconsistent. PT XYZ, as a strategic public service company, faces challenges in optimizing employee productivity, such as punctuality, work quality, and innovation. This study aims to analyze the influence of work environment and work motivation on employee productivity at PT XYZ using a quantitative approach through a survey of 48 active employees in the General Affairs & Property Assets division, Archives section. The data were analyzed using multiple linear regression with SPSS version 26. The results show that partially, the work environment has no significant effect on productivity (p = 0.180), while work motivation has a positive and significant effect (p = 0.000). Simultaneously, work environment and work motivation have a significant influence on employee productivity. These findings emphasize the importance of motivation as the main factor in improving employee performance. Therefore, the company is recommended to focus on strategies to increase motivation through incentives, self-development training, and the creation of clear and fair career paths.